2022
DOI: 10.1007/s42729-022-00993-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Plant Growth–Promoting Agent Mitigates Salt Toxicity in Barley (Hordeum vulgare L.) by Activating Photosynthetic, Antioxidant Defense, and Methylglyoxal Detoxification Machineries

Abstract: Developing and applying a novel plant growth–promoting agent (PGPA; a micronutrient-amino acid chelated compound developed from autolysis yeast cells) in alleviating salt stress toxicity can be the best alternative option environmentally and economically. High-performance liquid chromatography (HPLC) showed that the assembled PGPA is rich in nucleobases than yeast extract (> 56-fold). This study, as a first investigation, was aimed to evaluate PGPA’s potential role in reducing oxidative injury induced by sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…In addition to enhancing the activities of antioxidant enzymes, EBL and/or Spm foliage applications also contribute to AsA-GSH cycle modulation. Both AsA and GSH play a key role in ROS detoxification [62]. In the present study, when maize plants encounter water shortage environments, EBL and/or Spm treatments significantly meliorated the content of AsA and GSH, suggesting that treated plants could rely on antioxidants to maintain cellular redox homeostasis under stressful conditions.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In addition to enhancing the activities of antioxidant enzymes, EBL and/or Spm foliage applications also contribute to AsA-GSH cycle modulation. Both AsA and GSH play a key role in ROS detoxification [62]. In the present study, when maize plants encounter water shortage environments, EBL and/or Spm treatments significantly meliorated the content of AsA and GSH, suggesting that treated plants could rely on antioxidants to maintain cellular redox homeostasis under stressful conditions.…”
Section: Discussionsupporting
confidence: 46%
“…MDA is one of the products of cell membrane lipid peroxidation which damages cell membranes, finally leading to electrolyte extravasation and subsequent changes in the EL. The level of MDA and EL, therefore, reflect the degree of cell membrane integrity and are regarded as critical physiological indicators of plant senescence [62]. Our study shows that under drought stress, the application of EBL and/or Spm decreased the MDA and EL levels in the leaves.…”
Section: Discussionmentioning
confidence: 61%
“…Overproduction and buildup of ROS, which result in oxidative damage, can be brought by salt stress (Talaat et al 2022b). In this study, wheat leaves under salt stress produced an excessive amount of H 2 O 2 (Fig.…”
Section: Discussionmentioning
confidence: 60%
“…Soil salinization has detrimental impacts on plant development, reducing crop yields (Kaya et al 2020;Talaat and Shawky 2022;Talaat et al 2022b). Our results revealed that salt stress significantly (p < 0.05) hindered wheat development (Figs.…”
Section: Discussionmentioning
confidence: 64%
“…Osmolyte biosynthesis is critical for maintaining osmotic potential, metabolic activity, and water uptake under saline conditions [ 6 ]. Additionally, enzymatic and non-enzymatic antioxidants can scavenge effectively the excessive reactive oxygen species (ROS) generated during salt stress [ 7 , 8 , 9 , 10 , 11 ]. Ionic status inside the plant cell is also very important for plant salt tolerance because the excess of salt ions in the cytoplasm disrupts ion homeostasis, inhibits plant growth, and affects water transport [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%